Pengaruh Loan To Deposit Ratio, Return On Assets, Net Interest Margin Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Perbankan Di Bursa Efek Indonesia Tahun 2018-2021 - Bagus Ketut Rai Krisna; Ni Wayan Alit Erlina Wati; Putu Nuniek Hutnaleontina (UNHI Press, 2023)
In making an investment decision, investors will pay attention to many things, one of which is related to financial reports. Good financial reports will give investors an idea of the company's ability in the future. There are many things that investors consider when making an investment, including the Loan to Lending Ratio (LDR), Return On Assets (ROA), and Net Interest Margin (NIM). This observation was carried out to see how the influence of these factors can have an impact on firm value. This study will focus on the banking sector with a total sample of 40 companies used as the base group in the study. where analyzed using multiple linear regression analysis techniques, this observation obtained the results of the loan to deposit ratio having a negative and insignificant effect on the value of banking sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. ROA can affect the value of the company. NIM has no effect on firm value